A comparative study on the effect of streptokinase between diabetic and non-diabetic myocardial infarction patients - Nur-; A.K.M. Akhtaruzzaman; Md. Anup Rahman Chowdhury; A.K.M. Mosharrof Hossain; Sudhangshu Ranjan Dey (Bangladesh Pharmacological Society, 2008)
A prospective interventional study was carried out to compare the thrombolytic effect of streptokinase between diabetic and non-diabetic myocardial infarction patients. Out of 187 study subjects with acute ST segment elevation myocardial infarction (STEMI), admitted at coronary care unit, 126 patients were non-diabetic and 61 patients were diabetic. Streptokinase was administered to all patients. Resolution (reduction) of elevated ST segment was evaluated after 90 minutes of streptokinase administration. Successful reperfusion (≥70% ST-resolution) was significantly higher in non-diabetic than diabetic (p<0.001), while failed reperfusion (<30% ST resolution) was significantly higher in diabetic patients (p<0.001). It may be concluded that diabetes mellitus might affect the thrombolytic outcome of acute myocardial infarction patients with diabetes mellitus.